Low-temperature-gradient crystallization for multi-inch high-quality perovskite single crystals for record performance photodetectors. (January 2019) - Liu, Yucheng; Zhang, Yunxia; Yang, Zhou; Feng, Jiangshan; Xu, Zhuo; Li, Qingxian; Hu, Mingxin; Ye, Haochen; Zhang, Xu; Liu, Ming; Zhao, Kui; Liu, Shengzhong(Frank)
Graphical abstract: Abstract: With their excellent optoelectronic properties, the practical application of single-crystalline organolead halide perovskite materials is now limited by the lack of a method to prepare high-quality perovskite single crystals in large dimension. Herein, we report our development of a low-temperature-gradient crystallization (LTGC) method for high-quality CH3 NH3 PbBr3 (MAPbBr3 ) perovskite single crystals with lateral dimension as large as two inches. The theoretical analysis suggests that a small temperature gradient should be used to restrain the growth condition, particularly the solution concentration, within the optimal single-crystal-growth (OSCG) zone. The solubility curve as a function of temperature reveals a sharp turning point at ∼60 °C, across which the first-order solubility derivative (dC/dT) shows very different behaviors: below this temperature, the dC/dT changes dramatically as the temperature increases, while above this temperature, the dC/dT enters a plateau where further temperature change has little effect on the derivative, meaning that one can attain both a substantial crystal growth rate and crystallization yield below this temperature. Utilizing this discovery, a MAPbBr3 single crystal as large as 47 × 41 × 14 mm is obtained with high quality via the LTGC method. The single crystal exhibits the best optoelectronic quality among all MAPbBr3 materials reported in the literature, including the best trap state density, mobility, carrier lifetime, and diffusion length. These superior optoelectronic properties are further transferred into a high-performance planar photodetector. The device exhibits high operational stability, high external quantum efficiency (13, 453%), excellent detectivity as high as 8 × 10 13 Jones, and a fast response speed as quick as 15.8 μs. To our knowledge, both the detectivity and the response speed are the best among all MAPbBr3 devices reported to date. The unique synthesis method and excellent crystalline quality of the perovskite single crystals make them promising candidates for the next generation of optoelectronic devices.